Synthesis and Characterization of Some New Carbazolyloxy Substituted Oxazinane Derivatives - Reddy, A.R.; Mukkanti, K.; Chakravarthy, A.K.; Reddy, P.P. (Asian Journal of Chemistry, 2010)
Some new carbazolyloxy substituted oxazinane derivatives such as morpholinonyl, morpholinedionyl and morpholinyl were synthesized by cyclizing the corresponding carbazolyloxy propanolamine moiety using different two carbon sources.